Sintering Temperature Effect on Phase Formation, Microstructure and Electrical Properties of Modified KNLNTS Solid Solution Prepared via the Solid-State Combustion Technique - Chittakorn Kornphom; Pichittra Thawong; Suprakorn Khiwoon; Naratip Vittayakorn; Theerachai Bongkarn (Integrated ferroelectrics, 2023)
In this study, the effect of sintering temperature (1000–1100 °C for 2 h) on phase formation, phase transition, microstructure and electrical properties of lead-free piezoelectric (K0.44Na0.52Li0.04)(Nb0.84Ta0.10Sb0.06)O3 (KNLNTS) solid solution with 0.3 wt%Bi2O3 + 0.4 wt%Fe2O3 + 0.2 wt%CuO additive (abbreviate as modified KNLNTS) was investigated. Modified KNLNTS ceramics were synthesized by the solid-state combustion technique using glycine as fuel. The modified KNLNTS powders were prepared using the calcination condition of 650 °C for 2 h. The XRD pattern of all sintered ceramics exhibited a pure perovskite phase. Using Rietveld refinement to analyze the phase formation showed that the modified KNLNTS ceramics had co-existing phases of orthorhombic and tetragonal in all sintered ceramics and the orthorhombic phase increased when the sintering temperature increased. The average grain size, TO-T, Tc, Pr and Ec increased with increasing sintering temperature. At the sintering temperature of 1025 °C, the modified KNLNTS ceramic showed the best electrical properties (Cε ≈ 6745, Smax ≈0.274% and d*33 ≈ 548 pm/V). The good electrical properties of the modified KNLNTS ceramics makes them good candidates for lead-free applications to replace Pb-based ceramics.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Nuclear materials and radiation effects